Mrs. Doubtfire - Columbus, Chris; Williams, Marsha Garces; Williams, Robin, 1952 July 21-; Radcliffe, Mark, 1952-; Singer, Randi Mayem; Dixon, Leslie; Field, Sally; Brosnan, Pierce; Fierstein, Harvey, 1954-; Prosky, Robert, 1930-2008.; Fine, Anne.; Twentieth Century-Fox Film Corporation; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
Daniel Hillard is no ordinary father, so when he learns his ex-wife needs a housekeeper, he applies for the job. With the perfect wig, a little makeup and a dress for all occasions, he becomes Mrs. Doubtfire, a devoted British housekeeper who is hired on the spot. Free to be the "woman" he never knew he could be, the disguised Daniel creates a whole new life with his entire family.
disc 1. Feature film -- disc 2. Special features.
Based upon "Alias Madame Doubtfire" by Anne Fine.
Originally produced as a motion picture in 1993.
Special features: Disc 1 : Deleted, alternate, and extended scenes. Disc 2 : From man to Mrs. featurette; the evolution of Mrs. Doubtfire featurette; Aging gracefully-a look back at Mrs. Doubtfire featurette; behind-the-scenes photo gallery; conversation with animator Chuck Jones; animation sequences; original pencil test; makeup application and tests; Robin Williams improvisation scenes; Meet Mrs. Doubtfire publicity featurette; trailers, TV spots, and posters; photo galleries.
Director of photography, Donald McAlpine ; editor, Raja Gosnell ; music, Howard Shore ; production designer, Angelo Graham.
Robin Williams, Sally Field, Pierce Brosnan, Harvey Fierstein, Robert Prosky.
MPAA rating: PG-13.
Keywords: Fine, Anne -- Film adaptations; Housekeepers -- California -- San Francisco -- Drama; Divorced fathers -- California -- San Francisco -- Drama; Man-woman relationships -- California -- San Francisco -- Drama; Padre de familia -- California -- San Francisco -- Teatro; Relaciones humanas -- California -- San Francisco -- Teatro; San Francisco (Calif.) -- Drama; Comedy films; Film adaptations; Fiction films; Feature films; Video recordings for the hearing impaired